Thermoelectric transport in surface- and antimony-doped bismuth telluride nanoplates - Michael Thompson Pettes; Jaehyun Kim; Wei Wu; Karen C. Bustillo; Li Shi (APL Materials, 2016)
We report the in-plane thermoelectric properties of suspended (Bi1−xSbx)2Te3 nanoplates with x ranging from 0.07 to 0.95 and thicknesses ranging from 9 to 42 nm. The results presented here reveal a trend of increasing p-type behavior with increasing antimony concentration, and a maximum Seebeck coefficient and thermoelectric figure of merit at x ∼ 0.5. We additionally tuned extrinsic doping of the surface using a tetrafluoro-tetracyanoquinodimethane (F4-TCNQ) coating. The lattice thermal conductivity is found to be below that for undoped ultrathin Bi2Te3 nanoplates of comparable thickness and in the range of 0.2–0.7 W m−1 K−1 at room temperature.